1992
DOI: 10.1083/jcb.118.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-mediated cell-cell adhesion is perturbed by v-src tyrosine phosphorylation in metastatic fibroblasts.

Abstract: Abstract. Rat 3Y1 cells acquire metastatic potential when transformed with v-src, and this potential is enhanced by double transformation with v-src and v-los (Taniguchi, S., T. Kawano, T. Mitsudomi, G. Kimura, and T. Baba. 1986. Jpn. J. Cancer Res. 77:1193-1197. We compared the activity of cadherin cell adhesion molecules of normal 3Y1 cells with that of v-src transformed (SR3Y1) and v-src and v-los double transformed (fosSR3Y1) 3Y1 cells. These cells expressed similar amounts of P-cadherin, and showed simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
296
2
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 475 publications
(328 citation statements)
references
References 59 publications
20
296
2
9
Order By: Relevance
“…In the huiman gastric cancer cell line, HSC-39, mutation in the f-catenin gene that resulted in complete abolishment of E-cadherin-dependent cell-cell adhesion was observed, and transfection of the f-ctenin gene in the cells fully recovered the cell-cell adhesion (Kawanishi et al, 1995). We have previously reported (Matsuyoshi et al, 1992;Hamaguchi et al, 1993a) that cadherin dependent cell-cell adhesion was strongly erturbed upon tyrosine phosphorylation of f-catenin in RSV-transformed cells where cadherins and catenins were expressed and formed complexes as normal cells. Another pTyr-containing protein, pl20, was also identified as a major pTyr-containing protein in RSVtransformed cells whose phosphorylation closely correlated with cell transformation (Reynolds et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the huiman gastric cancer cell line, HSC-39, mutation in the f-catenin gene that resulted in complete abolishment of E-cadherin-dependent cell-cell adhesion was observed, and transfection of the f-ctenin gene in the cells fully recovered the cell-cell adhesion (Kawanishi et al, 1995). We have previously reported (Matsuyoshi et al, 1992;Hamaguchi et al, 1993a) that cadherin dependent cell-cell adhesion was strongly erturbed upon tyrosine phosphorylation of f-catenin in RSV-transformed cells where cadherins and catenins were expressed and formed complexes as normal cells. Another pTyr-containing protein, pl20, was also identified as a major pTyr-containing protein in RSVtransformed cells whose phosphorylation closely correlated with cell transformation (Reynolds et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…These proteins were known as major components of the cell adhesion system and their tyrosine phosphorylation showed good correlation with transforming activity of v-Src kinase (Schaller et al, 1992;Illic et al, 1995;Matsuyoshi et al, 1992;Hamaguchi et al, 1988Hamaguchi et al, , 1993aIllic et al, 1995;Reynolds et al, 1989Reynolds et al, , 1992. Thus, tyrosine phosphorylation of these proteins may perturb cell-cell adhesion and activate tumour cell movement, invasion and metastasis.…”
mentioning
confidence: 99%
“…The phosphotyrosine-containing proteins that we have now demonstrated in ECs exposed to TSP could be immunolocalized to the intercellular boundaries. Several nonreceptor PTKs are preferentially associated with the plasma membrane, including members of the src family (Tsukita et al, 1991;Matsuyoshi et al, 1992;Behrens et al, 1993;Hamaguchi et al, 1993). Src transformation increases tyrosine phosphorylation of cell-cell adherens junction proteins and diminishes cadherin-dependent, homophilic adhesion (Matsuyoshi et al, 1992;Volberg et al, 1992;Behrens et al, 1993;Hamaguchi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that multiple kinases and phosphatases regulate cadherin function, possibly each playing a role in a specific tissue and at a specific time during development. Overexpression of the nonreceptor tyrosine kinases Src (Matsuyoshi et al, 1992;Hamaguchi et al, 1993;Behrens et al, 1993), and Fer (Rosato et al, 1998) has been demonstrated to increase tyrosine phosphorylation of ␤-catenin (and p120 ctn ). Furthermore, a dominant-negative Src that interferes with function, or a Src-specific tyrosine kinase inhibitor induce cell-cell adhesion (Owens et al, 2000), further suggesting that Src plays an in vivo role in regulating the phosphotyrosine content of ␤-catenin and that suppression of tyrosine phosphorylation of ␤-catenin promotes formation of cadherin-mediated adhesions.…”
Section: Destabilizing Adhesions: Altering the Balance Between Phosphmentioning
confidence: 99%